1999
DOI: 10.1128/aem.65.9.4248-4251.1999
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Resistance to Hydrostatic Pressure among Strains of Food-Borne Pathogens

Abstract: Among food-borne pathogens, some strains could be resistant to hydrostatic pressure treatment. This information is necessary to establish processing parameters to ensure safety of pressure-pasteurized foods (N. Kalchayanand, A. Sikes, C. P. Dunne, and B. Ray, J. Food Prot. 61:425–431, 1998). We studied variation in pressure resistance among strains of Listeria monocytogenes, Staphylococcus aureus,Escherichia coli O157:H7, and Salmonellaspecies at two temperatures of pressurization. Early-stationary-phase cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(83 citation statements)
references
References 12 publications
4
74
1
4
Order By: Relevance
“…Recent years have seen significant research on the inactivation of microorganisms in foods by HP (Dogan & Erkmen, 2004;Smiddy et al, 2004Smiddy et al, , 2005Donaghy et al, 2007). Different microorganisms react with different degrees of resistance to HPP treatment, and indeed there can be vast HPP sensitivity among bacterial species and even strains (Alpas et al, 1999;Benito et al, 1999;Pagán & Mackey, 2000). Alpas et al (1999) reported viability losses of between 0.5 and 8.5 logs among pathogenic bacterial strains.…”
Section: Effect Of Hpp On Microbial Food Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have seen significant research on the inactivation of microorganisms in foods by HP (Dogan & Erkmen, 2004;Smiddy et al, 2004Smiddy et al, , 2005Donaghy et al, 2007). Different microorganisms react with different degrees of resistance to HPP treatment, and indeed there can be vast HPP sensitivity among bacterial species and even strains (Alpas et al, 1999;Benito et al, 1999;Pagán & Mackey, 2000). Alpas et al (1999) reported viability losses of between 0.5 and 8.5 logs among pathogenic bacterial strains.…”
Section: Effect Of Hpp On Microbial Food Safetymentioning
confidence: 99%
“…Different microorganisms react with different degrees of resistance to HPP treatment, and indeed there can be vast HPP sensitivity among bacterial species and even strains (Alpas et al, 1999;Benito et al, 1999;Pagán & Mackey, 2000). Alpas et al (1999) reported viability losses of between 0.5 and 8.5 logs among pathogenic bacterial strains. Prokaryotic cells tend to be more pressure resistant than eukaryotes (Patterson, 1999).…”
Section: Effect Of Hpp On Microbial Food Safetymentioning
confidence: 99%
“…A number of studies have reported that the resistance of a given species to a preservation technology may greatly vary amongst strains. Intraspecies resistance variation has been reported for several food preservation technologies (Patterson et al 1995;Alpas et al 1999;Benito et al 1999;Mañas et al 2000;Lado and Yousef 2003;Á lvarez et al 2003;Sherry et al 2004). Results published by Alpas et al (1999) showed that intraspecies variation in resistance to high hydrostatic pressure was remarkably wider for Staphylococcus aureus than for other micro-organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of microbial cells to UHHP depends on factors such as magnitude of pressure, pressurization time, temperature, initial number of cells, types of microbial cells, suspending media, and presence of antimicrobial substances (Mackey et al, 1995;Patterson et al, 1995;Benito et al, 1999;Alpas et al, 2000;Ritz et al, 2000;Furukawa et al, 2002). In view of the limited available information on the pressure resistance of foodborne pathogens (Metrick et al, 1989;Isaacs & Chilton, 1995;Patterson et al, 1995;Alpas et al, 1999Alpas et al, , 2000Benito et al, 1999), the current study was undertaken to determine the interactions between hydrostatic pressure, pressurization time, composition of media and cell age during pressurization on Listeria monocytogenes.…”
Section: Introductionmentioning
confidence: 99%